(untitled) (Research, Society and Development, 2024)
The construction industry has a significant impact on the environment, and improper disposal of its waste creates problems for cities. Proper management of this waste is crucial to promoting sustainable construction practices. Recycling waste materials, such as paper from cement sacks, stands out as a strategic opportunity in the construction industry. Ecological bricks can reuse waste by incorporating Kraft paper from cement bags. This study aimed to evaluate the performance of ecological bricks containing Kraft paper compared to ecological bricks without this addition. The production of both types of ecological bricks (18 samples) was started, one standard (9 samples) and the other with Kraft paper waste (9 samples). The comparative analysis of the properties of the ecological bricks suggests that those with added Kraft paper performed better, providing lighter and more sustainable alternatives to construction waste, and showing improvements in aesthetic properties such as color and texture, as well as density and mass.